PENGARUH PEMBERIAN UNSUR HARA MIKRO BORON TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium Cepa, L.) - Helmi Bakhtiar (Jurnal Agroristek, 2019)
The objectives of this research isto study the effect of the boron fertilizer to growth and yieldof onion. The implementation of experiements was conducted to see the respon of the onion by boron fertilizing doses (0-12kg/ha), the research has been conducted at Meunasah Lhee Village, Kecamatan Simpang Tiga, District of Pidie at Gadu Season (July to October) 2018. The result shows that boron affects the growth and yield of the onion. Boron fertilizing with the dose 6 kg/ha results the optimal growth, 15,13 cloves per clump, and the highest yield, which ic 25,20 ton/ha fresh cloves and 22,83 ton/ha dry cloves. Onion is a very strategic commodity. Beside has high economic value, among very kind vegetables it contributes inflation because the price is fluctuative dan the demand is raised from time to time. The onion yield is low at the farmer level, one of the reasons is fertilizer which not properly given. One the micro nutrients needed by plant is boron (B).Keywords:Â  micro fertilizer, boron, productivity, onion